The “Language of Law” and “More Probable Than Not”: Some Brief Thoughts - Kent Greenawalt (Washington University Law Quarterly, 1995)
By far the most testy moments of the conference arose out of the following problem. The Supreme Court had interpreted "knowingly" in a criminal statute regulating interstate commerce of child pornography to cover the age of participants, even though the placement of "knowingly" in the statutory provision would, according to standard usages of English grammar, lead to its not being applied to that element of the crime.! All participants at our conference fairly quickly acknowledged the following two truths: (1) the Court's construction did not fit ordinary English grammar, and (2) there might be appropriate (legal) reasons why statutory construction of a criminal statute would assign "knowingly" a force exceeding that indicated by ordinary English usage. This agreement was accompanied by sharp disagreement over whether one could properly speak of a "language of law" according to which "knowingly" had this special extension in criminal statutes. The lawyers said "yes"; the linguists said "no." No lawyer asserted that a clear practice of this sort actually exists, only that it might exist and that reasons relating to desirable culpability requirements might support it. The lawyers, at least this lawyer, attached no great significance to whether such a practice could be part of a "language," but we were exasperated by the linguists' assurance that it could not. Modest reading after the conference has reinforced my impression that the state of the discipline of linguistics leads scholars in that field to insist that languages have consistent rules of grammar. Therefore, the legal practice, if it existed, would have to be characterized in other terms. The basis for this underlying assumption about what are languages may be (I am not confident enough to assert that it is) the study of natural languages by linguists and their theories about the human mind as it relates to language. I (and others) insisted that whether the legal practice, if it existed, could be called an aspect of "legal language in the United States" was a matter neither of description nor normative judgment, but one of conceptualization. We claimed that it was somewhat arbitrary to preclude a conceptualization of "legal language" on the ground that the treatment of "knowingly" suggested no general, consistent, alternative grammatical practice, but rather amounted to an ad hoe deviation from ordinary practice. My views about this have not changed, but I now see two other questions as more important than the one on which we mainly focused. The most important practical question is how much it will count against an existing or proposed practice of interpretation that the practice violates ordinary rules of grammar. Most of the linguists, I think it is fair to say, believed that conformity with English grammar counts for quite a lot in a proposed interpretation. They did not deny that very strong (legal) reasons could override the argument in favor of an interpretation that conforms with ordinary grammar, but they assumed it would take very strong reasons to do so (once someone recognized the implications of ordinary grammar). Calling deviations a part of a "different language" ("Law English") might make it appear that weaker reasons could justify judicial disregard of ordinary English grammar. Just how strong reasons to deviate from ordinary English grammar need to be is a very complicated question. (For communications mainly from legislators to prosecutors and judges-such as designations about culpability-perhaps the reasons need be less strong than when communications are mainly to ordinary individuals and their lawyers.) My point here is merely that this question deserves careful independent judgment, and it should not be unthinkingly resolved, either way, by one's choice of characterization of a deviant linguistic practice. The second question is whether such deviant practices might be regarded as a fit study for linguists, with a potential for insights drawn from their discipline. Some lawyers at the conference expressed the view that the linguists should not simply suppose that a deviant practice is not their business because it is not (for them) part of a language. Perhaps there are reasons why linguists could not profitably study various subsystems that include certain deviations from standard grammatical usage (and do not include any consistent alternative grammar), but no one explained those reasons. Again, the question of aptness for examination by particular specialists should not be determined, either way, by one's choice of explanatory concepts.
Keywords: Linguistics